Tapered superlattice structure
By gradually changing the aluminum composition, thickness and period during the superlattice growth process, the gradient superlattice structure solves the limitations of the existing superlattice buffer layer in terms of stress treatment and application range, and significantly improves the performance of gallium nitride. The quality of the epitaxial wafer.
Patent Information
- Application Number
- CN202411410266.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing superlattice buffer layer has limitations in handling stress and defects, and has high requirements for process conditions and low application range. It is easy to cause stress balance collapse due to changes in the thickness of the substrate or epitaxial layer, causing lattice splitting and Warp abnormality.
The gradient super crystal structure is adopted, and the aluminum composition, thickness, and super crystal cycle is gradually changed during the growth of the superstiplapse, so that the stress is evenly distributed to the entire buffer layer to avoid local concentration or release of stress.
Effectively handle the stress and defect problems caused by heteroepitaxial growth, greatly expand the application range of the superlattice buffer layer, and improve the stress improvement and defect improvement effects of gallium nitride epitaxial wafers.
Smart Images

Figure CN119352169A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor manufacturing, and in particular relates to a gradient superlattice structure. Background Art
[0002] Epitaxy technology is a single crystal thin film deposition technology that deposits materials in the form of single crystals on a substrate to form an epitaxial layer. If the substrate material is the same as the epitaxial material, it is called homoepitaxy; if the substrate and epitaxial material are different, it is called heteroepitaxy. Heteroepitaxy will have a lattice mismatch due to the different lattice constants of the epitaxial material and the substrate. Lattice mismatch will cause lattice defects and increase stress in the epitaxial layer during the deposition process, affecting the quality of the epitaxial layer. Gallium nitride materials are affected by substrate technology, and commercial and large-scale gallium nitride substrates have not yet appeared on the market. Currently, silicon, sapphire, and silicon carbide materials are mainly used as substrates for gallium nitride materials on the market. The lattice mismatch between gallium nitride and various substrates is: -17% for silicon, 16.1% for sapphire, and 3.5% for silicon carbide. The general GaN epitaxial structure (from bottom to top): substrate / aluminum nitride (nucleation layer) / aluminum gallium nitride (buffer layer) / gallium nitride. The buffer layer is the key to heteroepitaxial growth. Its main function is to handle stress and reduce defects so that GaN crystals can grow on the low-defect epitaxial surface. The structural design of the buffer layer will affect the crystal quality and defect status of the GaN epitaxial layer, and thus affect the optical, electrical, and thermal properties of the manufactured chip.
[0003] There are two common buffer layer structure designs: stepped and superlattice. Figure 1 As shown, the main component of the stepped buffer layer is aluminum gallium nitride, which is easy to grow. The common structure is three layers of aluminum gallium nitride with high aluminum composition to low aluminum composition: Al0.75Ga0.25N / Al0.5Ga0.5N / Al0.25Ga0.75N. Because there are fewer interfaces and the aluminum composition of each layer is quite different, the stress will be concentrated at the interface of different aluminum compositions, resulting in poor ability to handle stress and defects. It is usually necessary to increase the thickness of the buffer layer to solve the problem of step buffer layer handling stress and defects. The main component of the superlattice buffer layer is aluminum gallium nitride, which is more difficult to grow. The structure is usually high aluminum gallium nitride and low aluminum gallium nitride, which are grown through periodic alternation. The high aluminum composition is usually between 100% and 85%, and the thickness is between 5-10nm; the low aluminum composition is usually between 15% and 0%, and the thickness is between 15-25nm.
[0004] like Figure 2As shown, in the existing superlattice buffer layer structure, a superlattice period usually includes a layer of aluminum gallium nitride composed of a high aluminum group and a layer of aluminum gallium nitride composed of a low aluminum group. The superlattice buffer layer is formed by repeated growth for dozens to hundreds of periods. This superlattice buffer layer can effectively deal with stress and defect problems through the alternation of tensile stress and compressive stress. However, the superlattice buffer layer has very high requirements for the stability of process conditions and has a low range of application. When the thickness of gallium nitride or the substrate changes slightly, the stress balance of the buffer layer will collapse, resulting in the lattice splitting of the epitaxial wafer and increased warping. Summary of the invention
[0005] To achieve the above objectives, the present invention provides a gradient superlattice structure, which can effectively deal with the stress and defect problems caused by heteroepitaxial growth and greatly improve the application range of the superlattice buffer layer.
[0006] A gradient superlattice structure comprises a plurality of groups of high-aluminum aluminum gallium nitride and a plurality of groups of low-aluminum aluminum gallium nitride, wherein the high-aluminum aluminum gallium nitride and the low-aluminum aluminum gallium nitride are arranged alternately, the aluminum composition of the high-aluminum aluminum gallium nitride is X, the aluminum composition of the low-aluminum aluminum gallium nitride is Y, the thickness of the high-aluminum aluminum gallium nitride is A, the thickness of the low-aluminum aluminum gallium nitride is B, the high-aluminum aluminum gallium nitride and the low-aluminum aluminum gallium nitride are arranged alternately for a period T, and at least one of them is a variable parameter; wherein T=A+B.
[0007] Furthermore, the aluminum composition X of the high aluminum composition aluminum gallium nitride is a fixed value, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters; wherein, T=A+B.
[0008] Furthermore, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all fixed values, and the aluminum composition X of the high aluminum composition aluminum gallium nitride and the aluminum composition Y of the low aluminum composition aluminum gallium nitride are both variable parameters; wherein, T=A+B.
[0009] Furthermore, the aluminum composition Y of the low aluminum composition aluminum gallium nitride is a fixed value, and the aluminum composition X of the high aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters; wherein, T=A+B.
[0010] Furthermore, the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride is a fixed value, the aluminum composition X of the high aluminum composition aluminum gallium nitride, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, and the thickness B of the low aluminum composition aluminum gallium nitride are all variable parameters; wherein, T=A+B.
[0011] Furthermore, the aluminum composition X of the high aluminum composition aluminum gallium nitride, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters, where T=A+B.
[0012] The advantages of the present invention are: the present invention provides a gradient superlattice structure, and the gradient superlattice growth technology used is to gradually change the aluminum composition, thickness, and superlattice period during the superlattice growth process, so that the stress is evenly distributed in the entire superlattice buffer layer, avoiding local concentration and release of stress.
[0013] The present invention is described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the stepped buffer layer structure.
[0015] Figure 2 It is a schematic diagram of the superlattice buffer layer structure.
[0016] Figure 3 It is a schematic diagram of the homoepitaxial structure.
[0017] Figure 4 It is a schematic diagram of the heteroepitaxial structure.
[0018] Figure 5 It is a schematic diagram of the lattice defect structure.
[0019] Figure 6 This is a schematic diagram of the existing superlattice structure.
[0020] Figure 7 This is a schematic diagram of a gradient superlattice structure. Figure 1 .
[0021] Figure 8 This is a schematic diagram of a gradient superlattice structure. Figure 2 .
[0022] Fig. 9 This is a schematic diagram of a gradient superlattice structure. Figure 3 .
[0023] Fig.10 This is a schematic diagram of a gradient superlattice structure. Figure 4 .
[0024] Fig.11 This is a schematic diagram of a gradient superlattice structure. Figure 5 . DETAILED DESCRIPTION
[0025] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose, the specific implementation methods, structural features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and embodiments.
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the description of the present invention, it is necessary to understand that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "aligned", "overlap", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0028] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features; in the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0029] Example 1
[0030] like Figure 3 , Figure 4 As shown, in heteroepitaxial technology, superlattice buffer layer is a common structural design to deal with stress and defects caused by lattice mismatch.
[0031] Epitaxial materials are deposited on substrates to form single crystal thin films. The stress caused by the substrate on the thin film will affect the maximum growth thickness (limit thickness) of the thin film. When the limit thickness is exceeded, the thin film begins to split. During the growth process, lattice mismatch will cause atoms to need additional energy to form bonds with the substrate; some atoms with insufficient energy cannot overcome the energy barrier to form bonds, which will form defects, such as Figure 5 shown.
[0032] like Figure 6 As shown, the superlattice buffer layer is generally grown through a fixed period, with two different thicknesses and compositions alternating and repeating, so that the film in each period will not exceed the limit thickness and split. As the overall thickness of the superlattice increases, the stress will gradually release, and the lattice size (lattice constant) will gradually tend to the lattice constant of the epitaxial material, so that the epitaxial material can overcome the surface potential energy, allowing atoms to be deposited on the superlattice buffer layer to form a single crystal film.
[0033] A superlattice structure with fixed period, thickness, and composition will cause stress to be excessively concentrated in dozens of superlattice periods close to the substrate with higher defect density. When the thickness variation of the substrate and epitaxial layer exceeds the range that the superlattice can withstand, the stress will be released locally on the surface of the superlattice film, causing lattice splitting and warping abnormalities.
[0034] This growth method has high requirements for raw material quality control and process equipment maintenance, and has a low tolerance range.
[0035] This embodiment provides a gradient superlattice structure, which distributes stress evenly throughout the superlattice buffer layer by gradually changing the aluminum composition, thickness, and superlattice period during the superlattice growth process, thereby avoiding local concentration and release of stress.
[0036] The gradient superlattice structure comprises a plurality of groups of high-aluminum aluminum gallium nitride and a plurality of groups of low-aluminum aluminum gallium nitride, wherein the high-aluminum aluminum gallium nitride and the low-aluminum aluminum gallium nitride are arranged alternately, the aluminum composition of the high-aluminum aluminum gallium nitride is X, the aluminum composition of the low-aluminum aluminum gallium nitride is Y, the thickness of the high-aluminum aluminum gallium nitride is A, the thickness of the low-aluminum aluminum gallium nitride is B, the period T of the alternating arrangement of the high-aluminum aluminum gallium nitride and the low-aluminum aluminum gallium nitride is at least one of which is a variable parameter; wherein T=A+B.
[0037] The aluminum composition of the above-mentioned gradient superlattice structure changes from high to low: that is, X i+1 >X i or X i+1 =X i , Y i+1 >Y i or Y i+1 =Y i ; The thickness of the superlattice high aluminum composition changes from high to low: that is, A i+1 i or A i+1 =A i ; The thickness of the superlattice low aluminum composition changes from low to high: that is, B i+1 >B i or B i+1 =B i ; Superlattice period changes from low to high: T i+1 >Ti or T i+1 = T i ; The thickness ratio of the high-aluminum composition to the low-aluminum composition in the superlattice changes from large to small (A / B): A i+1 / B i+1 < A i / B i , where n represents the total number of periods of the aluminum gallium nitride superlattice, and 1 ≤ i ≤ n - 1.
[0038] Aluminum composition:
[0039] In the first period of the aluminum gallium nitride superlattice, the aluminum composition (X, X1, X 1’ ) ranges from 70% to 100% (70% < X, X1, X 1’ ≤ 100%), and the aluminum composition (Y, Y1, Y 1’ ) of the low-aluminum composition ranges from 0% to 100% (0% < Y, Y1, Y 1’ ≤ 100%).
[0040] In the last period (n) of the aluminum gallium nitride superlattice, the aluminum composition (X, X n , X n’ ) ranges from 0% to 100% (0% < X, X n , X n’ ≤ 100%), and the aluminum composition (Y, Y n , Y n’ ) of the low-aluminum composition ranges from 0% to 30% (0% < Y, Y n , Y n’ ≤ 30%).
[0041] For the intermediate periods of the aluminum gallium nitride superlattice, it can be a linear change or a non-linear change, as long as it meets the requirement that the aluminum composition of the above-mentioned graded superlattice structure changes from high to low.
[0042] Thickness:
[0043] In the first period of the aluminum gallium nitride superlattice, the thickness (A, A1) of the high-aluminum composition ranges from 0 nm to 20 nm (0 nm < A, A1 ≤ 20 nm), and the thickness (B, B1) of the low-aluminum composition ranges from 0 nm to 40 nm (0 nm < B, B1 ≤ 40 nm).
[0044] In the last period (n) of the aluminum gallium nitride superlattice, the thickness (A, A n ) of the high-aluminum composition ranges from 0 nm to 20 nm (0 nm < A, A n ≤ 20 nm), and the thickness (B, B n ) of the low-aluminum composition ranges from 0 nm to 40 nm (0 nm < B, Bn ≦40nm).
[0045] The period of the aluminum gallium nitride superlattice in the middle can be changed linearly or nonlinearly, as long as the thickness change requirement of the gradient superlattice structure mentioned above is met.
[0046] Rate of change:
[0047] In the AlGaN superlattice, the difference in aluminum composition between the i-th period and the i+1-th period is between 0% and 50% (0% <X i+1 –X i ≦50%), the aluminum composition of low aluminum composition varies between 0% and 50% (0% <Y i+1 –Y i ≦50%). The thickness of high aluminum composition varies from 0nm to 20nm (0nm i+1 –A i ≦20nm), the thickness of low aluminum components varies from 0nm to 40nm (0nm i+1 –B i ≦40nm). The thickness ratio of high and low aluminum components varies from 0 to 1 (0 i / B i -A i+1 / B i+1 ≦1). The period difference is between 0nm and 60nm (0nm <T i+1 –T i ≦60nm).
[0048] In summary, the gradient superlattice structure uses a gradient superlattice growth technology that gradually changes the aluminum composition, thickness, and superlattice period during the superlattice growth process, so that the stress is evenly distributed in the entire superlattice buffer layer to avoid local concentration and release of stress.
[0049] Example 2
[0050] Further, such as Figure 7 As shown, this embodiment provides a gradient superlattice structure. In 100 cycles, the aluminum composition X of the high aluminum composition aluminum gallium nitride is 100% as a fixed parameter, and the aluminum composition Y of the low aluminum composition aluminum gallium nitride is i From 50% to 15%, Y i -Y i’ =0.1%, the thickness of the high aluminum composition aluminum gallium nitride A i The thickness B of the low aluminum composition aluminum gallium nitride changes from 10nm to 2nm. i The period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride is alternating. i From 15nm to 32nm, both are variable parameters; among them, T i =A i +B i In this embodiment, the stress of the GaN epitaxial wafer is improved by 80% and the defect is improved by 70%.
[0051] Example 3
[0052] Further, such as Figure 8 As shown, this embodiment provides a gradient superlattice structure. In 150 cycles, the aluminum composition Y of the low aluminum composition aluminum gallium nitride is 5% as a fixed parameter, and the aluminum composition X of the high aluminum composition aluminum gallium nitride is i From 95% to 50%, X i -X i’ =0.15%, thickness of high aluminum composition aluminum gallium nitride A i The thickness of low-aluminum aluminum gallium nitride B changes from 10nm to 2nm i From 10nm to 30nm, high aluminum composition aluminum gallium nitride and low aluminum composition aluminum gallium nitride are arranged alternately with a period of T i From 20nm to 32nm, both are variable parameters; among them, T i =A i +B i In this embodiment, the stress of the GaN epitaxial wafer is improved by 30%, and the defect is improved by 30%.
[0053] Example 4
[0054] Further, such as Fig. 9 As shown, this embodiment provides a gradient superlattice structure. In 100 periods, the thickness A of the high aluminum composition aluminum gallium nitride is 7nm, the thickness B of the low aluminum composition aluminum gallium nitride is 16nm, and the period T of alternating arrangement of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride is 23nm, which are all fixed parameters. The aluminum composition X of the high aluminum composition aluminum gallium nitride is i From 90% to 50%, X i -X i’ =0.1%, the aluminum composition of the low aluminum composition aluminum gallium nitride is Y i From 50% to 15%, Y i -Y i’ =0.25%, all of which are variable parameters; wherein, T=A+B. In this embodiment, the stress of the GaN epitaxial wafer is improved by 60%, and the defect is improved by 50%.
[0055] Example 5
[0056] Further, such as Fig.10As shown, this embodiment provides a gradient superlattice structure. In 150 periods, the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are alternately arranged. The period T is 25nm, which is a fixed parameter. The aluminum composition X of the high aluminum composition aluminum gallium nitride is i From 85% to 50%, X i -X i’ =0.08%, the aluminum composition of the low aluminum composition aluminum gallium nitride is Y i From 50% to 5%, Y i -Y i’ =0.2%, thickness A of high aluminum composition aluminum gallium nitride i The thickness of low-aluminum aluminum gallium nitride B changes from 7nm to 3nm i From 18nm to 22nm, both are variable parameters; where T=A i +B i In this embodiment, the stress of the GaN epitaxial wafer is improved by 70% and the defect is improved by 60%.
[0057] Example 6
[0058] Further, such as Fig.11 As shown, this embodiment provides a gradient superlattice structure. Within 200 cycles, the aluminum composition of the high aluminum composition aluminum gallium nitride is X i From 99% to 50%, X i -X i’ =0.1%, the aluminum composition of the low aluminum composition aluminum gallium nitride is Y i From 40% to 5%, Y i -Y i’ =0.1%, the thickness of the high aluminum composition aluminum gallium nitride A i The thickness B of the low aluminum composition aluminum gallium nitride changes from 10nm to 2nm. i The change from 7nm to 25nm, the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are alternately arranged with a period T i From 17nm to 27nm, all are variable parameters, among which, T i =A i +B i In this embodiment, the stress of the GaN epitaxial wafer is improved by 90% and the defect is improved by 50%.
[0059] Example 7
[0060] The gradient superlattice structure described in the above-mentioned embodiments 2 to 6, the method of controlling the gradient (X, Y) of the aluminum composition of the aluminum gallium nitride superlattice is as follows:
[0061] The gradient superlattice structure described in Example 2 is prepared by using an Aixtron G5 HT epitaxial growth device, wherein the aluminum source is trimethyl aluminum and the gallium source is trimethyl gallium. First, the pressure and temperature of the containers of trimethyl aluminum and trimethyl gallium, and the volume flow of trimethyl aluminum and trimethyl gallium are adjusted, and the molar flow ratio of trimethyl aluminum to trimethyl gallium is set to 50%: molar flow of trimethyl aluminum / (molar flow of trimethyl aluminum+molar flow of trimethyl gallium). In a superlattice period, when growing aluminum gallium nitride with a high aluminum composition, the valve of trimethyl aluminum is opened and the valve of trimethyl gallium is closed, and the aluminum composition X of the aluminum gallium nitride with a high aluminum composition is 100%; when growing aluminum gallium nitride with a low aluminum composition, the valve of trimethyl aluminum is opened and the valve of trimethyl gallium is opened to form a superlattice period of aluminum gallium nitride with a low aluminum composition. In the following superlattice cycles, the low-aluminum composition aluminum gallium nitride is grown alternately, and the volume flow of trimethylaluminum is gradually reduced and the volume flow of trimethylgallium is increased, so that the molar flow ratio of trimethylaluminum to trimethylgallium decreases by 0.35% each cycle until the 100th cycle, when the aluminum group (Y 100 ) reaches 15%; at the same time, the thickness of high aluminum composition aluminum gallium nitride (A i ), as the volume flow rate of trimethylaluminum decreases, it changes from 10nm to 2nm; the thickness of low aluminum composition aluminum gallium nitride (B i ), as the volume flow rate of trimethylgallium increases, it changes from 5nm to 30nm; at this time, the superlattice thickness period (T i ) changes from 15nm to 32nm, where T i =A i +B i .
[0062] The gradient superlattice structure described in Example 3 is prepared by using an Aixtron G5 HT epitaxial growth device, wherein the aluminum source is trimethyl aluminum, which is divided into two groups, high and low aluminum compositions; the gallium source is trimethyl gallium, which is divided into two groups, high and low aluminum compositions. First, the container pressure and temperature of trimethyl aluminum and trimethyl gallium, and the volume flow of trimethyl aluminum and trimethyl gallium are adjusted respectively, and the molar flow ratio of trimethyl aluminum and trimethyl gallium is set to 95% of the high aluminum composition and 5% of the low aluminum composition: molar flow of trimethyl aluminum / (molar flow of trimethyl aluminum+molar flow of trimethyl gallium). In a superlattice period, when growing aluminum gallium nitride with a high aluminum composition, the valve of trimethyl aluminum with a high aluminum composition is opened, and the valve of trimethyl gallium with a high aluminum composition is opened; when growing aluminum gallium nitride with a low aluminum composition, the valve of trimethyl aluminum with a low aluminum composition is opened, and the valve of trimethyl gallium with a low aluminum composition is opened, so as to form a superlattice period of aluminum gallium nitride with a low aluminum composition. In the following superlattice period, the low aluminum composition aluminum gallium nitride is grown alternately, and the volume flow rate of trimethylaluminum with high aluminum composition is gradually reduced and the volume flow rate of trimethylgallium with high aluminum composition is increased, so that the aluminum composition (X i ) changes from 95% to 50%; at the same time, the growth time of high aluminum composition aluminum gallium nitride is reduced to make the thickness of high aluminum composition aluminum gallium nitride (A i ) changes from 10nm to 2nm; increasing the growth time of low aluminum composition aluminum gallium nitride, so that the thickness of low aluminum composition aluminum gallium nitride (B i ) changes from 10nm to 30nm; at this time, the superlattice thickness period (T i ) changes from 20nm to 32nm, where T i =A i +B i .
[0063] The gradient superlattice structure described in Example 4 is prepared by using an Aixtron G5 HT epitaxial growth device, wherein the aluminum source is trimethyl aluminum, which has two groups, divided into high and low aluminum compositions; the gallium source is trimethyl gallium, which has two groups, divided into high and low aluminum compositions. First, the container pressure and temperature of trimethyl aluminum and trimethyl gallium, and the volume flow of trimethyl aluminum and trimethyl gallium are adjusted respectively, and the molar flow ratio of trimethyl aluminum and trimethyl gallium is set to 90% of the high aluminum composition and 50% of the low aluminum composition: molar flow of trimethyl aluminum / (molar flow of trimethyl aluminum+molar flow of trimethyl gallium). In a superlattice period, when growing aluminum gallium nitride with a high aluminum composition, the valve of trimethyl aluminum with a high aluminum composition is opened, and the valve of trimethyl gallium with a high aluminum composition is opened; when growing aluminum gallium nitride with a low aluminum composition, the valve of trimethyl aluminum with a low aluminum composition is opened, and the valve of trimethyl gallium with a low aluminum composition is opened, to form a superlattice period of aluminum gallium nitride with a low aluminum composition. In the next superlattice period, aluminum gallium nitride with a low aluminum composition is grown alternately. When the aluminum gallium nitride with high aluminum composition is grown, the volume flow rate of trimethylaluminum with high aluminum composition is gradually reduced, the volume flow rate of trimethylgallium with high aluminum composition is increased, and the change rate of the volume flow rates of trimethylaluminum and trimethylgallium is controlled to make the aluminum composition (X i ) changes from 90% to 50%, and the thickness (A) of the high aluminum composition aluminum gallium nitride is fixed at 7nm; when the low aluminum composition aluminum gallium nitride is grown, the volume flow rate of trimethylaluminum with low aluminum composition is reduced, the volume flow rate of trimethylgallium with low aluminum composition is increased, and the change rate of the volume flow rates of trimethylaluminum and trimethylgallium is controlled to make the aluminum composition (Y i ) changes from 50% to 15%, and the thickness (B) of the low-aluminum aluminum gallium nitride is fixed at 16nm; at this time, the superlattice thickness period (T) is fixed at 23nm, where T=A+B.
[0064] The gradient superlattice structure described in Example 5 is prepared by using an Aixtron G5 HT epitaxial growth device, wherein the aluminum source is trimethyl aluminum, which has two groups, divided into high and low aluminum compositions; the gallium source is trimethyl gallium, which has two groups, divided into high and low aluminum compositions. First, the container pressure and temperature of trimethyl aluminum and trimethyl gallium, and the volume flow of trimethyl aluminum and trimethyl gallium are adjusted respectively, and the molar flow ratio of trimethyl aluminum and trimethyl gallium is set to 85% of the high aluminum composition and 50% of the low aluminum composition: molar flow of trimethyl aluminum / (molar flow of trimethyl aluminum+molar flow of trimethyl gallium). In a superlattice period, when growing aluminum gallium nitride with a high aluminum composition, the valve of trimethyl aluminum with a high aluminum composition is opened, and the valve of trimethyl gallium with a high aluminum composition is opened; when growing aluminum gallium nitride with a low aluminum composition, the valve of trimethyl aluminum with a low aluminum composition is opened, and the valve of trimethyl gallium with a low aluminum composition is opened, to form a superlattice period of aluminum gallium nitride with a low aluminum composition. In the next superlattice period, aluminum gallium nitride with a low aluminum composition is grown alternately. When the aluminum gallium nitride with high aluminum composition is grown, the volume flow rate of trimethylaluminum with high aluminum composition is gradually reduced, the volume flow rate of trimethylgallium with high aluminum composition is increased, and the change rate of the volume flow rates of trimethylaluminum and trimethylgallium is controlled to make the aluminum composition (X i ) changes from 85% to 50%, the thickness of high aluminum composition aluminum gallium nitride (A i ) changes from 7nm to 3nm; when growing low aluminum composition aluminum gallium nitride, the volume flow rate of trimethylaluminum with low aluminum composition is reduced, the volume flow rate of trimethylgallium with low aluminum composition is increased, and the change rate of the volume flow rates of trimethylaluminum and trimethylgallium is controlled to make the aluminum composition (Y i ) changes from 50% to 5%, the thickness of low aluminum composition AlGaN (B i ) changes from 18nm to 22nm; at this time, the superlattice thickness period (T) is fixed at 25nm, where T=A i +B i .
[0065] The gradient superlattice structure described in Example 6 is prepared by using an Aixtron G5 HT epitaxial growth device, wherein the aluminum source is trimethyl aluminum, which has two groups, divided into high and low aluminum compositions; the gallium source is trimethyl gallium, which has two groups, divided into high and low aluminum compositions. First, the container pressure and temperature of trimethyl aluminum and trimethyl gallium, and the volume flow of trimethyl aluminum and trimethyl gallium are adjusted respectively, and the molar flow ratio of trimethyl aluminum and trimethyl gallium is set to 99% of the high aluminum composition and 40% of the low aluminum composition: molar flow of trimethyl aluminum / (molar flow of trimethyl aluminum+molar flow of trimethyl gallium). In a superlattice period, when growing aluminum gallium nitride with a high aluminum composition, the valve of trimethyl aluminum with a high aluminum composition is opened, and the valve of trimethyl gallium with a high aluminum composition is opened; when growing aluminum gallium nitride with a low aluminum composition, the valve of trimethyl aluminum with a low aluminum composition is opened, and the valve of trimethyl gallium with a low aluminum composition is opened, to form a superlattice period of aluminum gallium nitride with a low aluminum composition. In the next superlattice period, aluminum gallium nitride with a low aluminum composition is grown alternately. When the aluminum gallium nitride with high aluminum composition is grown, the volume flow rate of trimethylaluminum with high aluminum composition is gradually reduced, the volume flow rate of trimethylgallium with high aluminum composition is increased, and the change rate of the volume flow rates of trimethylaluminum and trimethylgallium is controlled to make the aluminum composition (X i ) changes from 99% to 50%, the thickness of high aluminum composition aluminum gallium nitride (A i ) changes from 10nm to 2nm; when growing low aluminum composition aluminum gallium nitride, reducing the volume flow rate of trimethylaluminum with low aluminum composition, increasing the volume flow rate of trimethylgallium with low aluminum composition, and controlling the change rate of the volume flow rates of trimethylaluminum and trimethylgallium, so that the aluminum composition (Y i ) changes from 40% to 5%, the thickness of low aluminum composition aluminum gallium nitride (B i ) changes from 7nm to 25nm; at this time, the superlattice thickness period (T i ) changes from 17nm to 27nm, where T i =A i +B i .
[0066] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A gradient superlattice structure, comprising a plurality of groups of high-aluminum aluminum gallium nitride and a plurality of groups of low-aluminum aluminum gallium nitride, wherein the high-aluminum aluminum gallium nitride and the low-aluminum aluminum gallium nitride are arranged alternately, characterized in that: The aluminum composition of high aluminum gallium nitride is X, the aluminum composition of low aluminum gallium nitride is Y, the thickness of high aluminum gallium nitride is A, the thickness of low aluminum gallium nitride is B, the high aluminum gallium nitride and the low aluminum gallium nitride are alternately arranged with a period T, and at least one of them is a variable parameter; wherein T=A+B.
2. A gradient superlattice structure according to claim 1, characterized in that: The aluminum composition X of the high aluminum composition aluminum gallium nitride is a fixed value, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters; wherein T=A+B.
3. The gradient superlattice structure according to claim 1, characterized in that: The aluminum composition Y of the low aluminum composition aluminum gallium nitride is a fixed value, and the aluminum composition X of the high aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters; wherein T=A+B.
4. The gradient superlattice structure according to claim 1, characterized in that: The thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all fixed values, and the aluminum composition X of the high aluminum composition aluminum gallium nitride and the aluminum composition Y of the low aluminum composition aluminum gallium nitride are both variable parameters; wherein, T=A+B.
5. The gradient superlattice structure according to claim 1, characterized in that: The alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride is a fixed value, the aluminum composition X of the high aluminum composition aluminum gallium nitride, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, and the thickness B of the low aluminum composition aluminum gallium nitride are all variable parameters; wherein, T=A+B.
6. The gradient superlattice structure according to claim 1, characterized in that: The aluminum composition X of the high aluminum composition aluminum gallium nitride, the aluminum composition Y of the low aluminum composition aluminum gallium nitride, the thickness A of the high aluminum composition aluminum gallium nitride, the thickness B of the low aluminum composition aluminum gallium nitride, and the alternating arrangement period T of the high aluminum composition aluminum gallium nitride and the low aluminum composition aluminum gallium nitride are all variable parameters, where T=A+B.